Successful treatment of invasive mycobacterium infection with interferon beta in a patient with Interferon-Gamma Receptor 1 deficiency - Fayhan Alroqi; Abduarahman Almutairi; Moza Alhammadi; Shatha Alhamdi (Elsevier, 2024)
Mendelian susceptibility to mycobacterial disease (MSMD) is caused by approximately 21 genetic defects, including a mutation in Interferon-Gamma Receptor 1 (IFNGR1). IFNGR1 deficiency leads to a loss of cellular responsiveness to type II Interferon (IFN-γ), which plays a significant role in controlling intracellular bacteria. This study explored the response of IFN-β therapy in a patient with partial IFNGR1 deficiency to treat invasive mycobacterial infection. The biological therapy was used successfully as an adjuvant to anti-mycobacterial medications to treat a 17-year-old girl with partial IFNGR1 deficiency who presented with a recurrent mycobacterial infection that extended to her central nervous system, which resulted in clinical and radiological improvement. This report suggests that activation of type I IFN through Signal Transducers and Activators of Transcription1 (STAT1) could bypass the early IFN-γ signaling defects and activate IFN-γ production. For that reason, IFN-β might be used as a beneficial adjuvant therapy for managing extensive central nervous system mycobacterial infection, especially in patients with IFNGR1 deficiency.